2004
DOI: 10.1023/b:catl.0000020537.33875.46
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of PdCxover Pd-Based Catalysts in Vapor-Phase Vinyl Acetate Synthesis: Does a Pd–Au Alloy Catalyst Resist Carbide Formation?

Abstract: The formation of Pd carbide (PdC x ) during the synthesis of vinyl acetate (VA) was investigated over Pd/SiO 2 catalysts with two different Pd particle sizes, as well as over a Pd-Au/SiO 2 mixed-metal catalyst. XRD data show that PdC x was produced in the pure Pd catalysts after reaction based on the downshift of the Pd (111) and (200) XRD features. The smaller Pd particles showed greater resistance to the formation of PdC x . The XRD and XPS data are consistent with formation of a PdC x species at the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 17 publications
5
72
1
Order By: Relevance
“…Han et al have suggested, employing ex situ XRD, that Pd nanocrystals below 2.4 nm were more resistant to carbide formation than their larger counterparts due to the metal nonmetal transition that could lead to drastically altered chemical properties. 44 This does not conflict with our findings and suggests that there is probably a critical size (ca. 2.5 nm 44 ) above which size does not significantly impact carbide formation.…”
Section: ■ Results and Discussionsupporting
confidence: 68%
“…Han et al have suggested, employing ex situ XRD, that Pd nanocrystals below 2.4 nm were more resistant to carbide formation than their larger counterparts due to the metal nonmetal transition that could lead to drastically altered chemical properties. 44 This does not conflict with our findings and suggests that there is probably a critical size (ca. 2.5 nm 44 ) above which size does not significantly impact carbide formation.…”
Section: ■ Results and Discussionsupporting
confidence: 68%
“…The influence on the catalytic properties of carbon residing in the subsurface region was described previously [14][15][16]. Since these are all ex situ studies the question of stability of intermediates is an issue.…”
Section: -Pentyne Hydrogenation On Pd Based Catalystsmentioning
confidence: 99%
“…1,2 The outstanding properties of alloys in heterogeneous catalysis result from a number of effects, e.g., a lowered barrier for a specific chemical reaction, an increased selectivity, 3,4 and an enhanced resistance against contamination and poisoning. 5,6 The formation of alloy particles on thin oxide films has recently been characterized using scanning tunneling microscopy ͑STM͒ and electron and infrared spectroscopy. [7][8][9] In contrast to bulk alloys, the intermixing in small particles depends on several additional parameters, such as diffusivity, nucleation and growth of the compounds on the oxide support, their surface free energy and miscibility, and the thermodynamic alloying conditions.…”
Section: Introductionmentioning
confidence: 99%